PENDAMPINGAN DESAIN TATA LETAK GUDANG EFISIEN MENGGUNAKAN METODE ARC–ARD BERBASIS SIMULASI FLEXSIM DI PT MIKRON PRESISI INDONESIA - Raka Fahrezi Putrapriatna; Mariyadi, Budiyan; Inten Tejaasih (Jurnal Pengabdian Indonesia (JPI), 2026)
This study aims to design the warehouse tata letak at PT MIKRON PRESISI INDONESIA that experiences post-relocation irregularities in production facilities, along with adjustments to the area area and available rental costs. The absence of a racking system and clear classification of goods has caused the storage, retrieval, and work safety processes to not run efficiently. The research approach uses a qualitative descriptive method by collecting data through field observations, interviews, and documentation. The tata letak design was carried out by implementing the Activity Relationship Chart (ARC) and Activity Relationship Diagram (ARD) methods, then tested through simulations using FlexSim software with two operator scenarios. The simulation results showed that the proposed alternative tata letak design was able to improve the workflow by grouping goods into seven categories and arranging shelves based on the level of proximity of activities. However, the utilization rate of operators is still relatively low, namely 17.65% and 19.78%, due to the periodic pattern of goods arrival and efficient search times due to a more structured storage system. These findings indicate opportunities for human resource optimization through reducing the number of operators or adjusting workloads. The resulting tata letak design makes a practical contribution to improving warehouse space efficiency and operations, and can be used as a reference for applications for companies with similar characteristics.